Design and application of a new type of wound ruler for measuring pressure injuries (一种新型压力性损伤测量尺的设计与应用) - XIA Tian (夏天); XI Wenxuan (席雯萱); CHEN Yongfang (陈永芳); SHI Lin (师琳); LUO Jie (罗杰); ZHAO Yuntong (赵匀彤); GAO Xiaoyu (高小雨); ZHUO Jiajia (卓加加) (中西医结合护理)
Pressure injuries are local damage to the skin or underlying tissue caused by the combined action of pressure and shear forces, usually in areas where bones protrude. The correct understanding and effective management of pressure injuries by medical personnel are crucial to the prevention and treatment of pressure sores. Accurate assessment of pressure injuries classification and measurement of wound size is an important basis for pressure injuries management. This study introduces the design and use method of a utility model of wound ruler for measuring pressure injuries, which is simple in structure and easy to use, and can effectively improve the rapid and accurate assessment of pressure injuries by medical staff, and provide a new idea and method for improving the quality of patient care and promoting wound healing. (压力性损伤是由于压力和剪切力共同作用导致的皮肤或皮下组织的局部损伤, 通常发生在骨骼突出部位。准确评估压力性损伤的分级和测量伤口的大小, 是进行压疮管理的重要基础。本研究介绍一款实用新型压力性损伤测量尺的设计和使用方法, 其结构简单, 使用方便, 有助于医务人员快速准确评估压力性损伤情况, 为改善患者护理质量和促进伤口愈合提供可靠数据。)